Lithium ion battery negative electrode material loaded with lithium-loving packaging material and preparation method of lithium ion battery negative electrode material
Selective deposition and stable encapsulation in the negative electrode material of lithium-ion battery through heterogeneous seed growth technology, the volume expansion problem of the negative electrode material of lithium-ion battery is solved, the circulation and rate performance of the material is improved, and the material is enhanced. security.
Patent Information
- Application Number
- CN202411168723.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-27
AI Technical Summary
The volume expansion rate of existing lithium-ion battery negative electrode materials is large when deintercalated with lithium, resulting in particle differentiation, poor circulation stability, and poor contact between active substances and conductive agents, which cannot meet the requirements of high energy density and safety.
Selective deposition and stable encapsulation of the lithium deembedding process through heterogeneous seed growth technology to prepare lithium-prone encapsulation materials, including amino functionalized microsphere substrates, adsorbed lithium-prone encapsulation materials and coated with carbon layers, etching Form a porous structure.
It realizes rapid embedding and disengagement of lithium, improves lithium storage capacity, reduces lithium intercalation, and avoids alloy formation, which significantly improves the circulation, rate performance and safety performance of the material.
Smart Images

Figure CN119208551A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a negative electrode material for lithium ion batteries loaded with a lithium-philic packaging material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have become an ideal power source for portable devices, power systems and energy storage. Therefore, it is of great significance to develop new negative electrode materials with high specific energy, good safety, long cycle life and low cost to match the new generation of lithium-ion batteries. At present, mature negative electrode materials for lithium-ion batteries are mainly graphite-based carbon materials, which store lithium by intercalating lithium ions between carbon materials. The theoretical specific capacity is 372mAh / g, which cannot meet the high energy density demand for lithium-ion batteries in the future. Through research, it was found that carbon substitutes such as Al, Sn, Sb, Si, etc. can form alloyed metals and their alloy materials with Li, and the reversible lithium storage capacity is greatly improved compared with carbon materials. Among them, Si can form Li with lithium. 22 Si5 alloy has a theoretical capacity of 4200mAh / g, but the volume expansion rate of Si-based negative electrode materials is large (>300%) when lithium is inserted and removed. The volume expansion will cause problems such as particle differentiation and shedding, poor cycle stability, and poor contact between active materials and conductive agents and binders. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0004] To this end, the embodiments of the present invention provide a lithium-ion battery negative electrode material loaded with a lithium-philic encapsulation material and a preparation method thereof. The present invention is the first to prepare a new high-performance negative electrode material by selectively depositing and stably encapsulating the lithium insertion and extraction process through heterogeneous seed growth.
[0005] The present invention provides a method for preparing a negative electrode material of a lithium ion battery loaded with a lithium-philic packaging material, comprising the following steps:
[0006] (a) functionalizing the microsphere substrate with amino groups;
[0007] (b) adsorbing the lithium-philic encapsulation material onto the amino-functionalized microsphere substrate;
[0008] (c) coating the outer layer of the microsphere substrate on which the lithium-philic encapsulation material is adsorbed with a carbon layer.
[0009] In some embodiments, after step (c), a microsphere substrate etching step (d) is further included, wherein the microsphere substrate etching is performed by etching the microsphere substrate with potassium hydroxide solution or hydrofluoride under the condition of adding IPA to make the microsphere substrate porous.
[0010] In some embodiments, the method further includes preparing a microsphere substrate before step (a), wherein the microsphere substrate is spherical.
[0011] In some embodiments, the step (b) further includes preparing lithium-philic encapsulating material nanoparticles.
[0012] In some embodiments, the microsphere substrate is at least one of graphite, carbon, silicon, and tin materials.
[0013] In some embodiments, the lithium-philic encapsulating material is at least one of Mg, Zn, Au, Al, and r-GO.
[0014] In some embodiments, the process of coating the outer layer of the microsphere substrate with a carbon layer in step (c) is to first coat the outer layer of the microsphere substrate with an organic carbon material, and then calcine to convert the organic carbon material into inorganic carbon.
[0015] In some embodiments, the organic carbon material is formaldehyde resin or phenolic resin.
[0016] In some embodiments, in step (a), aminosilane coupling agent and isopropyl alcohol are used to functionalize the microsphere substrate with amino groups.
[0017] On the other hand, the present invention provides a negative electrode material for a lithium ion battery loaded with a lithium-philic encapsulating material, which is prepared by the method for preparing a negative electrode material for a lithium ion battery loaded with a lithium-philic encapsulating material of the present invention.
[0018] Compared with the prior art, the beneficial effects of the present invention are:
[0019] The present invention deposits a lithium-philic encapsulation material on the surface of a microsphere substrate, realizes quantitative deposition under the premise of achieving uniform deposition, eliminates lithium intercalation and deintercalation overpotential, realizes rapid lithium intercalation and deintercalation, and improves the rate performance of negative electrode materials by increasing the lithium storage capacity; lithium intercalation is effectively reduced through lithium encapsulation, and the formation of silicon-lithium alloys and other alloys is avoided, effectively solving the problems of low first efficiency, expansion, powdering and shedding of negative electrode materials, and growth of lithium dendrites, and greatly improving the cycle performance, rate performance and safety performance of the material; in addition, the present invention can also improve its performance by etching the microsphere substrate to make it porous according to needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0021] Figure 1 A flow chart of the method for preparing a negative electrode material for a lithium-ion battery loaded with a lithium-philic encapsulating material according to the present invention;
[0022] Figure 2The flow chart of the method for preparing a negative electrode material for a lithium-ion battery loaded with a lithium-philic encapsulating material including an etching step of the present invention;
[0023] Figure 3 This is a process flow chart when the microsphere substrate is silicon dioxide;
[0024] Figure 4 This is a process flow framework diagram when the microsphere substrate is silicon dioxide. DETAILED DESCRIPTION
[0025] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0026] A lithium-ion battery negative electrode material loaded with a lithium-philic packaging material and a preparation method thereof according to an embodiment of the present invention are described below with reference to the accompanying drawings.
[0027] like Figure 1 As shown, a method for preparing a negative electrode material of a lithium-ion battery loaded with a lithium-philic packaging material of the present invention comprises the following steps:
[0028] (a) functionalizing the microsphere substrate with amino groups;
[0029] (b) adsorbing the lithium-philic encapsulation material onto the amino-functionalized microsphere substrate;
[0030] (c) A carbon layer is coated on the outer layer of the microsphere substrate adsorbed with the lithium-philic encapsulation material.
[0031] In step (a), the amino silane coupling agent and isopropanol are used to amino-functionalize the microsphere substrate. Before step (a), the process also includes the preparation of the microsphere substrate, which is spherical, that is, the microsphere substrate is first prepared and then amino-functionalized. Before step (b), the process also includes the preparation of lithium-philic encapsulation material nanoparticles, that is, nano-sized lithium-philic encapsulation material is first prepared and then adsorbed on the amino-functionalized microsphere substrate.
[0032] In some embodiments, Figure 2 As shown, after step (c), a microsphere substrate etching step (d) is also included. The microsphere substrate etching is performed by etching the microsphere substrate with potassium hydroxide solution or hydrofluoride under the condition of adding IPA to make it porous, thereby improving the performance of the negative electrode material.
[0033] The microsphere substrate is at least one of graphite, carbon, silicon, and tin materials. Taking silicon as an example, the microsphere substrate can be SiOx.
[0034] The lithium-philic packaging material is at least one of Mg, Zn, Au, Al, and r-GO. The lithium-philic material is used to achieve stable packaging of lithium to avoid directly forming a silicon-lithium alloy to increase the lithium storage capacity, improve the volume expansion effect of the negative electrode material to improve the performance of the negative electrode material, and thus improve the overall performance of the lithium-ion battery.
[0035] In step (c), the process of coating the outer layer of the microsphere substrate with a carbon layer is to first coat the outer layer of the microsphere substrate with an organic carbon material, and then calcine the organic carbon material to convert it into inorganic carbon, wherein the organic carbon material is formaldehyde resin or phenolic resin. It is understandable that other suitable types of organic carbon can also be selected according to actual conditions.
[0036] Taking silicon dioxide as an example, the process flow chart of the present invention is as follows Figure 3 As shown, the process includes the following steps: preparing SiO2 precursor; modifying the surface of SiO2; depositing nanoparticles of lithium-philic encapsulation material on the surface of SiO2; preparing SiO2 coated with resin; carbonizing the resin to obtain a silicon-carbon composite material with lithium-philic encapsulation material; and etching to obtain a porous silicon-carbon composite material with lithium-philic encapsulation material. The process flow diagram is shown in Figure 4 As shown, lithium is deposited inside the lithium-philic encapsulating material or inside the silicon.
[0037] Embodiment 1:
[0038] (1) Add 9 ml of tetraethyl orthosilicate to a mixture of 90 ml of isopropanol and 15 ml of water;
[0039] (2) 9 ml of 1 M ammonium hydroxide was added to the solution while stirring at 500 r / min, and the reactants were left at room temperature for 2 h until all TEOS was decomposed into silica spheres;
[0040] (3) After centrifugation three times and washing with IPA and water, all particles were dispersed in 120 ml IPA by ultrasonic treatment;
[0041] (4) After stirring the solution at 60° C. for 24 h, 1 ml of (3-aminopropyl)triethoxysilane (APTES) was added, the solution was centrifuged three times, washed once with IPA and twice with deionized water, and then the silica spheres were dispersed in 25 ml of water by ultrasonic treatment;
[0042] (5) Dilute 1 ml of sodium citrate solution (10%) in 100 ml of water, heat and boil, and quickly inject 200 μl of chloroauric acid (HAuCl4, 0.5 M). React for 5 min, and then cool the solution to room temperature. The average diameter of the prepared gold NPs is about 20 nm. Add 100 ml of the gold NPs colloidal suspension to the silica suspension in three batches, so that the silica spheres change from white to pink and finally to purple.
[0043] (6) All particles were dispersed in 250 ml of water, sonicated to coat the formaldehyde resin, and then 9 ml of hexadecyltrimethylammonium bromide (CTAB, 10 mM) and 0.9 ml of ammonium hydroxide (1 M) were added and stirred for 15 min;
[0044] (7) Add 300 mg of resorcinol and 420 μl of formaldehyde solution and stir for 9 hours;
[0045] (8) heating to 600 °C at a heating rate of 2 °C / min, holding for 2 h, and then heating to 900 °C at a heating rate of 10 °C / min, holding for 3 h, so that the sample is kept at 900 °C to carbonize all the resin shells;
[0046] (9) The silica template was etched by hydrofluoride (HF, 10%). After etching, the sample was filtered and washed, and the solid product was dried under vacuum at 80° C. for 24 h.
[0047] Embodiment 2:
[0048] (1) Add 9 ml of tetraethyl orthosilicate to a mixture of 90 ml of isopropanol and 15 ml of water;
[0049] (2) 9 ml of 1 M ammonium hydroxide was added to the solution while stirring at 500 r / min, and the reactants were left at room temperature for 2 h until all TEOS was decomposed into silica spheres;
[0050] (3) After centrifugation three times and washing with IPA and water, all particles were dispersed in 120 ml IPA by ultrasonic treatment;
[0051] (4) After stirring the solution at 60° C. for 24 h, 1 ml of (3-aminopropyl)triethoxysilane (APTES) was added, the solution was centrifuged three times, washed once with IPA and twice with deionized water, and then the silica spheres were dispersed in 25 ml of water by ultrasonic treatment;
[0052] (5) Dilute 1 ml of sodium citrate solution (10%) in 100 ml of water. After heating to boil, quickly inject 300 μl of magnesium chloride (0.5 M), react for 5 minutes, and then cool the solution to room temperature. The average diameter of the prepared magnesium NPs is about 20-30 nm; 100 ml of magnesium NPs colloidal suspension is added to the silica suspension in 3 batches and evenly dispersed;
[0053] (6) All particles were dispersed in 250 ml of water, sonicated to coat the formaldehyde resin, and then 9 ml of hexadecyltrimethylammonium bromide (CTAB, 10 mM) and 0.9 ml of ammonium hydroxide (1 M) were added and stirred for 15 min;
[0054] (7) Add 400 mg of resorcinol and 500 μl of formaldehyde solution and stir for 10 hours;
[0055] (8) heating to 600 °C at a heating rate of 2 °C / min, holding for 2 h, and then heating to 900 °C at a heating rate of 10 °C / min, holding for 3 h, so that the sample is kept at 900 °C to carbonize all the resin shells;
[0056] (9) The silica template was etched by hydrofluoride (HF, 10%). After etching, the sample was filtered and washed, and the solid product was dried under vacuum at 80° C. for 24 h.
[0057] Embodiment 3:
[0058] (1) Add 9 ml of tetraethyl orthosilicate to a mixture of 90 ml of isopropanol and 15 ml of water;
[0059] (2) 9 ml of 1 M ammonium hydroxide was added to the solution while stirring at 500 r / min, and the reactants were left at room temperature for 2 h until all TEOS was decomposed into silica spheres;
[0060] (3) After centrifugation three times and washing with IPA and water, all particles were dispersed in 120 ml IPA by ultrasonic treatment;
[0061] (4) After stirring the solution at 60° C. for 24 h, 1 ml of (3-aminopropyl)triethoxysilane (APTES) was added, the solution was centrifuged three times, washed once with IPA and twice with deionized water, and then the silica spheres were dispersed in 25 ml of water by ultrasonic treatment;
[0062] (5) Dilute 1 ml of sodium citrate solution (10%) in 100 ml of water, heat and boil, and quickly inject 200 μl of chloroauric acid (HAuCl4, 0.5 M). React for 5 min, and then cool the solution to room temperature. The average diameter of the prepared gold NPs is about 20 nm. Add 100 ml of the gold NPs colloidal suspension to the silica suspension in three batches, so that the silica spheres change from white to pink and finally to purple.
[0063] (6) All particles were dispersed in 250 ml of water, sonicated to coat the formaldehyde resin, and then 9 ml of hexadecyltrimethylammonium bromide (CTAB, 10 mM) and 0.9 ml of ammonium hydroxide (1 M) were added and stirred for 15 min;
[0064] (7) Add 300 mg of resorcinol and 420 μl of formaldehyde solution and stir for 9 hours;
[0065] (8) The sample was heated to 600 °C at a heating rate of 2 °C / min and kept at this temperature for 2 h. Then, the sample was heated to 900 °C at a heating rate of 10 °C / min and kept at this temperature for 3 h. The sample was kept at 900 °C to carbonize all the resin shells.
[0066] Comparative Example 1:
[0067] (1) Add 9 ml of tetraethyl orthosilicate to a mixture of 90 ml of isopropanol and 15 ml of water;
[0068] (2) 9 ml of 1 M ammonium hydroxide was added to the solution while stirring at 500 r / min, and the reactants were left at room temperature for 2 h until all TEOS was decomposed into silica spheres;
[0069] (3) All particles were dispersed in 250 ml of water, sonicated to coat the formaldehyde resin, and then 9 ml of hexadecyltrimethylammonium bromide (CTAB, 10 mM) and 0.9 ml of ammonium hydroxide (1 M) were added and stirred for 15 min;
[0070] (4) Add 300 mg of resorcinol and 420 μl of formaldehyde solution and stir for 9 hours;
[0071] (5) heating to 600 °C at a heating rate of 2 °C / min, holding for 2 h, and then heating to 900 °C at a heating rate of 10 °C / min, holding for 3 h, so that the sample is kept at 900 °C to carbonize all the resin shells;
[0072] (6) The silica template was etched by hydrofluoride (HF, 10%). After etching, the sample was filtered and washed, and the solid product was dried under vacuum at 80° C. for 24 h.
[0073] The negative electrode materials obtained in Example 1, Example 2, Example 3 and Comparative Example 1 were characterized and their electrochemical properties were tested. The preparation process of the button cell is as follows:
[0074] Material preparation: respectively select the negative electrode active material, conductive agent, SBR, and CMC in Examples 1-3 and Comparative Example 1, and the material ratio is: negative electrode active material: conductive agent: CMC: SBR: water = 100:1.5:1.5:3:130.
[0075] Electrode sheet production: The negative electrode slurry is evenly coated on the copper foil, and the coating thickness and uniformity are controlled. The coated electrode sheet is placed in a vacuum oven and dried at a certain temperature (usually 80-120°C) for a period of time to remove moisture. The dried electrode sheet is cut into circular electrode sheets of appropriate size using a slicer.
[0076] Battery assembly: Operate in a glove box filled with inert gas to ensure that the water and oxygen content is extremely low (generally required to be less than 0.1ppm), place the negative electrode sheet in the negative electrode shell of the button battery, then place the diaphragm on it, and drip an appropriate amount of electrolyte to fully soak the diaphragm. Then put in the lithium sheet and cover the positive electrode shell, and use a battery packaging machine for packaging.
[0077] When the button cell was assembled for electrochemical performance testing, the negative electrode material was kept as the only variable. The test results are shown in Table 1 below.
[0078] Table 1 Electrochemical performance test data of button cells composed of materials in Example 1, Example 2, Example 3 and Comparative Example 1
[0079]
[0080] It can be seen from the data in the table that the negative electrode material prepared according to the method of the present invention has good initial capacity, initial coulombic efficiency and cycle.
[0081] By comparing Example 1 with Comparative Example 1, it can be seen that the initial capacity, initial coulombic efficiency and cycle performance of the negative electrode material without the lithium-philic encapsulation material are lower than those of the negative electrode containing the Au encapsulation material. The reason is presumed to be that by depositing the lithium-philic encapsulation material, the overpotential of lithium insertion and extraction is eliminated, the lithium storage capacity is increased, the rapid insertion and extraction of lithium is achieved, and the volume expansion rate of the material is reduced.
[0082] By comparing Examples 1 and 2 with Comparative Example 1, it can be seen that the deposition of different lithium-philic materials such as Mg / Au has little effect on the first capacity, first coulombic efficiency and cycle, and can improve the first efficiency and capacity retention, which are better than the negative electrode without encapsulation material.
[0083] By comparing Example 3 with Comparative Example 1, it can be seen that the composite negative electrode material with a lithium-philic encapsulation material has great advantages in terms of first effect and first reversible capacity compared with the composite negative electrode without a lithium-philic encapsulation material, even without etching and pore formation, and can significantly improve the performance of the negative electrode material, and has a good capacity retention rate after a long cycle. The reason is speculated to be: by depositing the lithium-philic encapsulation material, the overpotential of lithium insertion and extraction is eliminated, the lithium storage capacity is increased, and the rapid insertion and extraction of lithium is achieved.
[0084] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0085] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0086] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing a negative electrode material for a lithium-ion battery loaded with a lithium-philic encapsulation material, characterized in that: The following steps are involved: (a) functionalizing the microsphere substrate with amino groups; (b) adsorbing the lithium-philic encapsulation material onto the amino-functionalized microsphere substrate; (c) coating the outer layer of the microsphere substrate on which the lithium-philic encapsulation material is adsorbed with a carbon layer.
2. The method according to claim 1, characterized in that The method further comprises step (d) of etching the microsphere substrate to make it porous by using potassium hydroxide solution or hydrofluoride under the condition of adding IPA.
3. The method according to claim 1, characterized in that The microsphere substrate is spherical.
4. The method according to claim 1, characterized in that The lithium-philic encapsulating material is a nanoparticle.
5. The method according to claim 3, characterized in that The microsphere substrate is at least one of graphite, carbon, silicon and tin materials.
6. The method according to claim 4, characterized in that The lithium-philic packaging material is at least one of Mg, Zn, Au, Al, and r-GO.
7. The method according to claim 1, characterized in that The process of coating the outer layer of the microsphere substrate with a carbon layer in step (c) is to first coat the outer layer of the microsphere substrate with an organic carbon material, and then calcine to convert the organic carbon material into inorganic carbon.
8. The method according to claim 7, characterized in that The organic carbon material is formaldehyde resin or phenolic resin.
9. The method according to claim 1, characterized in that In the step (a), aminosilane coupling agent and isopropanol are used to carry out amino functionalization on the microsphere substrate.
10. A negative electrode material for a lithium-ion battery loaded with a lithium-philic encapsulation material, characterized in that: The negative electrode material is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium metal negative electrode of hollow carbon spheres loaded with silver particles and solid-state battery
CN114284501A
Porous carbon material and preparation method thereof, negative pole piece and lithium ion battery
CN115838163A
